The Use of Undo Process in Improving Self-Efficacy - Andy Sapta (International Journal of Trends in Mathematics Education Research, 2018)
The aims of this research are to know the use of the undo process method in the completion of the inverse function. This type of research is a quasi-experiment. The group used in this study consisted of two groups. One group as a control group uses conventional learning methods that use the conventional inverse method of solving conventional function, and one group as an experimental group which in learning use undo process method in solving inverse function. This research was conducted at SMA Negeri 1 Buntu Pane, Asahan Regency, North Sumatra province, Indonesia. The population of this study is the students of class XI IA in the academic year 2016/2017 even semester. The sample was obtained by using cluster random sampling method. The study sample is two classes of 5 existing classes. Implementation of this research by using the undo process method to student ability to solve the problem given. The technique of collecting data using test and questionnaire given to student which become sample. Research data show that by applying this method of learning can improve self-efficacy in the following material about inverse function.